2021
DOI: 10.1002/pros.24170
|View full text |Cite
|
Sign up to set email alerts
|

Does surgery benefit patients with oligometastatic or metastatic prostate cancer? – A retrospective cohort study and meta‐analysis

Abstract: Background: To evaluate long-term oncological outcomes of radical prostatectomy (RP) plus androgen deprivation therapy (ADT) in oligometastatic prostate cancer (PCa) patients.Methods: Our study included oligometastatic PCa patients hospitalized between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In total, 10 relevant studies [25][26][27][28][29][30][31][32][33][34] incorporating 888 patients were included in the present analysis after having met with study selection criteria (Table 1). All included prospective studies were considered to be of high quality (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 10 relevant studies [25][26][27][28][29][30][31][32][33][34] incorporating 888 patients were included in the present analysis after having met with study selection criteria (Table 1). All included prospective studies were considered to be of high quality (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…2019 [ 33 ] 49 ST 23 22.8(14-43) 65.2%(3-y) 65.2%(3-y) CRP 26 19.2(9-42) 76.9%(3-y) 76.9%(3-y) Shubin Si al. 2021 [ 34 ] 84 RP 27 76.67 ± 9.66 96.2%(3-y) 76.0%(5-y) -RP 57 76.42 ± 9.69 94.7%(3-y) 74.9%(5-y) Continuous variables were expressed as (mean±SD), mean (range) or median (IQR) PSA The nadir of prostate-specific antigen, CSS Cancer-specific survival, OS overall surviva, RP radical retropubic prostatectomy, CRP cytoreductive prostatectomy, RARP robot-assisted radical prostatectomy, ADT androgen deprivation therapy …”
Section: Methodsmentioning
confidence: 99%
“…3 B). Three studies assessed the OS of oligometastatic PCa, [ 7 , 12 , 13 ] and pooled data showed cytoreductive surgery did not significantly affect the OS (OR = 1.33, 95% CI 0.87–2.02, P = .19, Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis and retrospective cohort study [34] compared survival outcomes in the RP+ ADT vs ADTonly group of patients with OMPCa. The results suggest that the addition of surgery does not increase CRPC-free survival.…”
Section: P R E P R I N Tmentioning
confidence: 99%